Synthesis and Supramolecular Structure of 3,3'-Dibromo-1,1'-[butane-1,4-diyldioxybis(nitrilomethylidyne)]dibenzene - Sun, Yin-Xia; Meng, Wei-Sheng; Lan, Qing-Ying; Zhang, Xiao-Yan; Ma, Fei-Xia; Wang, Da-Seng (Asian Journal of Chemistry, 2013)
The compound, 3,3'-dibromo-1,1'-[butane-1,4-diyldioxybis(nitrilo-methylidyne)]dibenzene with the molecular formula C18H18N2O2Br2, was synthesized by the reaction of 3-bromobenzaldehyde with 1,4-bis(aminooxy) butane in ethanol. The molecule lies across a crystallographic inversion centre (symmetry code: -x, -y, -z) and adopts an extended form. Within the molecule, the two aromatic rings are aligned with the angle of 5.57(3)º, but extend in opposite directions from the tetramethylene bridge. In the crystal structure, weak intermolecular C-H···O hydrogen bonds and C-H···p stacking interactions link the title molecules into an infinite 3D supramolecular network structure.